An Anti-migration Self-expandable and Removable Metal Stent for Crohn's Disease Strictures: A Nationwide Study From GETAID and SFED. (27th October 2020) - Attar, Alain; Branche, Julien; Coron, Emmanuel; Privat, Jocelyn; Caillo, Ludovic; Chevaux, Jean-Baptiste; Vuitton, Lucine; Amiot, Aurélien; Belkhodja, Hichem; Dray, Xavier; Ponchon, Thierry; Bouhnik, Yoram; et al.
Abstract: Background and Aims: In Crohn's disease, strictures are frequent and may require surgical resection or endoscopic balloon dilation. An anti-migration, removable and shaped self-expandable metal stent is available. We evaluated its effectiveness and safety in a real-life setting. Methods: All centres were asked to collect retrospectively or prospectively all data on patients who had a stent for a stricture. The anti-migration stent [Hanarostent HRC-20-080-230—MITech, Seoul, South Korea] was maintained 7 days before its extraction during a second colonoscopy. Short- and long-term efficacy and safety outcomes were evaluated. Results: A total of 46 patients were enrolled. Strictures were anastomotic in 73.9% of cases. The median length of the stricture evaluated by cross-sectional imaging and during colonoscopy was 3.1 ± 1.7 and 2.7 ± 1.4 cm, respectively. Immediate success [no obstructive symptom at Day 30] was reported in 93.5% of cases (95% confidence interval [CI] = [86.3; 99.9]). Sixteen patients needed a new balloon dilation [ n = 8] or surgery [ n = 8]. The overall success rate [obstruction-free without any intervention] was 58.7% [ n = 27] after a median follow-up of 26 months [8–41 months]. No perforation occurred and three migrations were observed [6.5%]. Perianal disease (hazard ratio [HR] = 0.1 [0.02; 0.58]) and discontinuation of an immunosuppressant (0.12 [0.02; 0.86]), were associated with a lower probability of success, whereas performing imaging (HR = 5.3 [1.2; 23.5]) before stent placement was associated with success. Conclusions: The anti-migration stent is safe and effective in about half of patients, with no perforation reported in this study, and has an extremely low migration rate.